2018–2019 Florida Citrus Production Guide: Pesticide Resistance and Resistance Management - Lauren M. Diepenbrock; Megan M. Dewdney (EDIS)
This 4-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Lauren M. Diepenbrock and Megan M. Dewdney, and published by the Entomology and Nematology Department, May 2018.